Heterogeneous Clinical Phenotypes of dHMN Caused by Mutation in HSPB1 Gene: A Case Series - Xiya Shen; Jiawei Zhang; Feixia Zhan; Wotu Tian; Qingqing Jiang; Xinghua Luan; Xiaojie Zhang; Li Cao (Biomolecules, 2022)
Mutations in HSPB1 are known to cause Charcot-Marie-Tooth disease type 2F (CMT2F) and distal hereditary motor neuropathy (dHMN). In this study, we presented three patients with mutation in HSPB1 who were diagnosed with dHMN. Proband 1 was a 14-year-old male with progressive bilateral lower limb weakness and walking difficulty for four years. Proband 2 was a 65-year-old male with chronic lower limb weakness and restless legs syndrome from the age of 51. Proband 3 was a 50-year-old female with progressive weakness, lower limbs atrophy from the age of 44. The nerve conduction studies (NCS) suggested axonal degeneration of the peripheral motor nerves and needle electromyography (EMG) revealed chronic neurogenic changes in probands. Open sural nerve biopsy for proband 2 and the mother of proband 1 showed mild to moderate loss of myelinated nerve fibers with some nerve fiber regeneration. A novel p.V97L in HSPB1 was identified in proband 3, the other two variants (p.P182A and p.R127W) in HSPB1 have been reported previously. The functional studies showed that expressing mutant p.V97L HSPB1 in SH-SY5Y cells displayed a decreased cell activity and increased apoptosis under stress condition. Our study expands the clinical phenotypic spectrum and etiological spectrum of HSPB1 mutation.